The Influences of Land Use on the Urban Heat Island in Bucharest - B. URIŢESCU; N. IONAC; G. GRIGORAŞ (Aerul şi Apa: Componente ale Mediului, 2017)
The aim of the paper is to investigate the contribution of different land use types on the intensification/reduction of the Urban Heat Island (UHI) in the four seasons. The study was carried out in the Bucharest metropolitan area, the capital of Romania. To analyze the land use impact on the UHI, the following stages were performed: i) it was made a land use classification in three major classes (water, green areas and built-up-areas), which in their turn were divided into other categories (water bodies, parks, forests, industrial-commercial area, low density residential area, high density residential area); ii) the Landsat satellite images were selected, from which land surface temperature was derived; iii) a basic statistical analysis was performed based on which was determined the relationship between the land use type and land surface temperature. The study results shows that the industrial-commercial areas and the high density residential areas correspond to the highest values of the land surface temperatures, thus contributing to the intensification of the UHI phenomenon, regardless of the season, while the water bodies and the forests have the lowest values of the land surface temperatures, also regardless of the season.